Drainage Characteristics, Capillary Barrier Effect, and Diversion Length of Flat Earthen Roof of Historical Kemaliye Houses - Fidan, Aysenur Aslan; Berilgen, Mehmet Muhit (TAYLOR & FRANCIS INC, 2025)
Kemaliye houses stand out as remarkable examples of Anatolian architecture, renowned for their distinct mixed construction method and the utilization of diverse and sustainable materials. The flat earthen roof, constructed using local soils and traditional techniques, adds to the unique character of these houses. However, due to the need for roof maintenance, particularly in winter, residents have adopted modern roofing methods. In order to preserve the architectural integrity of historic houses, research into the mechanisms and performance of flat earthen roofs using local materials and original construction techniques is essential. To achieve this objective, original materials, and construction techniques were investigated with 1D infiltration laboratory tests and analyzed using numerical modelling. The results indicated the existence of a capillary barrier effect on the roofs. Additionally, water balance and diversion length of the roof is obtained through experimental study and numerical analysis. Furthermore, numerical analyses indicated that the capillary barrier effect may be reduced or weakened as a result of frost heave and the formation of desiccation cracks. Understanding these phenomena is a vital step in developing effective solutions for preserving and maintaining roofs in their original architectural form.
Keywords: Capillary barrier effect; conservation problems; desiccation crack; diversion length; flat earthen roof; frost heave; Kemaliye historical houses; precipitation; unsaturated flow; HYDRAULIC CONDUCTIVITY; PHYSICAL MODEL; COVERS; INFILTRATION; DESIGN; PERFORMANCE; HYSTERESIS; Architecture; Construction & Building Technology; Engineering